STUDI GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGELOLA SEKOLAH ADIWIYATA DI SMPS EHIPASSIKO SCHOOL BSD KOTA TANGERANG SELATAN - Roch Aksiadi; Aris Gumilar (Universitas Muhammadiyah Tangerang, 2020)
The problem that was raised by the researcher was the leadership study of the principal in managing the Adiwiyata program at the Ehipassiko Junior High School, South Tangerang City. The purpose of this study is to describe the leadership of the principal in managing the Adiwiyata program at Ehipassiko Junior High School, South Tangerang City. This study uses a qualitative approach. The subjects of this study were the Principal, Teachers, Staff, and Students of Ehipassiko Junior High School, South Tangerang City. The technique used in collecting data is by using observation, interviews and documentation. The validity of the data in this study uses credibility, transferability, dependability, and confirmability techniques. Data analysis uses the Miles and Huberman interactive model, namely data collection, data reduction, data appearance, and conclusion. The results of this study indicate that (1) the leadership style of the principal of Ehipassiko Junior High School, South Tangerang City in managing adiwiyata schools is to use a democratic approach and have succeeded in leading. (2) There are 4 stages that principals do in managing adiwiyata schools, namely environmentally sound policies, implementation of environment-based curricula, participatory based environmental activities, and management of environmentally friendly supporting facilities (3) School principals' constraints in managing Adiwiyata schools at Ehipassiko Junior High School, South Tangerang City, includes limited time, lack of environmental resources, students, teachers, staff who must always be controlled in implementing the Adiwiyata program. The school solution to overcome these obstacles is to continue to approach all components of the school, motivation, consultation with the school supervisor and requesting direction from the education consultant. From this research, it is expected (1) the school to improve the performance of schools that have now reached adiwiyata at the district / city level to become provincial adiwiyata schools, (2) teachers should be able to divide their time to adiwiyata program management towards the provincial level, so that they can eventually increase public trust in the Ehipassiko Junior High School, South Tangerang City.